APLIKASI TEKNOLOGI BIOPELET LIMBAH KOPI SEBAGAI BAHAN BAKAR ALTERNATIF DALAM RANGKA PENGEMBANGAN DESA MANDIRI ENERGI DI DESA JATIROKE KAWASAN SEKITAR HUTAN PENDIDIKAN GUNUNG GEULIS ITB - Anne Hadiyane; Alfi Rumidatul; Yayat Hidayat (LP2M Universitas Hasanuddin, 2021)
Abstract. The utilization of coffee skin waste is still a problem faced by members of farmer groups in Jatiroke Village, Jatinangor District, Sumedang Regency, West Java Province. The solution provided to address the problems of partners in the form of the application of biopelet making technology in the processing of coffee waste in the context of developing energy independent villages. The service activity program is carried out in four stages, namely a) Identification of problems; b) Program socialization; c) Education and training programs; and d) Monitoring and evaluation. The activities carried out with the Gunung Geulis coffee farmers group are a) Information program socialization; b) Training and mentoring the process of processing and making biopelet from coffee waste and c) monitoring and evaluating each phase of the activity. The results obtained after this activity is the achievement of increased knowledge and skills of Gunung Geulis coffee farmers in processing coffee waste into biopelet as an environmentally friendly alternative energy source. Abstrak. Pemanfaatan limbah kulit kopi masih menjadi permasalahan yang dihadapi anggota kelompok tani di Desa Jatiroke Kecamatan Jatinangor Kabupaten Sumedang Provinsi Jawa Barat. Solusi yang diberikan untuk menjawab permasalahan mitra berupa penerapan teknologi pembuatan biopelet pada proses pengolahan limbah kopi dalam rangka pengembangan desa mandiri energi. Program kegiatan pengabdian dilaksanakan dalam empat tahapan, yakni a) Indentifikasi masalah; b) Sosialisasi program; c) Program penyuluhan dan pelatihan; dan d) Monitoring dan evaluasi. Kegiatan yang dilaksanakan dengan kelompok petani kopi Gunung Geulis yakni: a) Sosialisasi program kegiatan; b) Pelatihan dan pendampingan proses pengolahan dan pembuatan biopelet dari limbah kopi dan c) monitoring dan evaluasi setiap tahapan kegiatan. Hasil yang diperoleh setelah kegiatan ini adalah tercapainya peningkatan pengetahuan dan keterampilan petani kopi Gunung Geulis dalam mengolah limbah kopi menjadi biopelet sebagai sumber energi alternatif yang ramah lingkungan.